Assessment of liposuction cannulas’ interior: insights from visual inspection using a borescope - Batista, Daniela Santos; Prado, Roberta Teixeira; Leone, Denise Rocha Raimundo; Carbogim, Fábio da Costa; Paula, Vanessa Albuquerque Alvim de; Oliveira, Adriana Cristina de; Alvim, Andre Luiz Silva (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Alterations in liposuction cannulas compromise their use and patient safety in healthcare services. Aim: to evaluate the interior of liposuction cannulas through visual inspection aided by a borescope. Design: this is a descriptive, quantitative study conducted at a materials and sterilization center of a public hospital in Minas Gerais, Brazil, from October 2023 to January 2024. Liposuction cannulas were randomly selected, chosen systematically. Visual inspection assisted by a borescope was conducted, and the data were recorded in a semi-structured instrument, analyzed using descriptive statistics. Results: Liposuction cannulas of sizes 3.0 mm and 4.0 mm were evaluated with equal frequency, as they are reusable devices without control regarding the number of sterilizations they have undergone since acquisition. The majority exhibited alterations detected through the borescope (66.7%), with notable occurrences of oxidation, stains, and/or discoloration (60.0%), residues or debris (33.3%), and grooves (25.0%). Implications: Tracking of liposuction cannulas identified alterations that compromise their usage, observed with the assistance of a borescope. The findings call for changes in current legislation within sterilization centers due to the absence of indication of this equipment as mandatory for aiding visual inspection.